Analysis of the Implementation of Active Fire Protection Systems in Disaster Mitigation at Regional General Hospital (RSUD) X - Fadhli, Muhammad (BKM Public Health and Community Medicine, 2024)
Purpose: This study aims to analyze the implementation of active fire protection systems at Regional General Hospital (RSUD) X. It focuses on the effectiveness of active protection systems, the factors influencing their implementation, and the challenges faced during implementation. Methods: This research employs a descriptive quantitative approach with a case study design to describe, explain, and summarize various conditions, situations, and phenomena. Respondents included the head of the Hospital Facilities Maintenance Installation (IPSRS). Data were collected through interviews, observations, and document reviews. The collected data were then analyzed descriptively. Results: Based on interviews and observations, the implementation rates of various fire protection measures were as follows: fire extinguishers (APAR) at 89.4%, sprinklers at 66.6%, hydrants at 63.6%, and fire alarms at 100%. Issues identified include broken and unreplaced sprinklers, inadequate spacing between sprinklers, hydrant boxes lacking equipment due to theft, and insufficient numbers of fire extinguishers. Conclusion: The active fire protection system at RSUD X faces several issues, such as broken and improperly spaced sprinklers and hydrant boxes, and missing equipment due to theft. There is also a shortage of fire extinguishers (APAR). Strategies to address these issues include identifying existing problems, prioritizing replacements in high-risk or critical areas such as public areas and easily flammable zones, and regularly maintaining and inspecting equipment according to a set schedule.